STUDENTS’ MISCONCEPTION IN RESPIRATORY PHYSIOLOGY - Afzal, M. Nasir (Journal of Ayub Medical College Abbottabad, 2004)
Background: Misconceptions in Physiology are common and are carried into later years of medical education, perhaps leading to difficulty in understanding Pathology and Medicine later on. To find the prevalence of misconceptions in Respiratory Physiology, one question was asked to 1st, 2nd, 3rd and 4th year MBBS students while they were still studying basic sciences and the response was analyzed accordingly. Methods: The question was asked What happens to the tidal volume during exercise? to 153 MBBS medical students during their first to fourth year medical education and they were asked to pick the right answer from three choices. Results: The correct answer was picked by 35 % of students from all four classes. Furthermore, class wise distribution of the data revealed that correct answer was given maximally by first year students (45%) and fourth year students (43%). But, only 27% and 8% of second and third year students answered the question correctly. Conclusion: This data shows the extent of prevalence of misconceptions in Respiratory Physiology among medical students during their years of medical education at one medical institute in Pakistan. Key words: Physiology, misconceptions, students, laboratory, tidal volume